Does the Reprocessing of Endoscopes Have to Take Place Immediately after Pre-Cleaning? A First Evaluation - Vanessa M Eichel; Jonas M Jabs; Samy Unser; Nico T Mutters; Martin Scherrer (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The recommendations on the time interval between pre-cleaning and reprocessing of endoscopes differ in international guidelines, with a low level of evidence. The aim of this study was to investigate the influence of postponing reprocessing on the reprocessing quality after pre-cleaning the flexible endoscopes. Methods We reprocessed 124 standardized test tubes simulating endoscope channels after soiling and contamination and determined the reprocessing performance. In addition, we examined contaminated gastroscopes, colonoscopes, and bronchoscopes. The duration of interim storage after pre-cleaning was 16 h for 100 test tubes and up to 24 h for 18 endoscopes. We determined the residual protein content and germ load as markers for cleaning and disinfection performance. In addition, we determined biofilm formation by photometry of crystal violet staining. Results All test tubes and flexible endoscopes showed residual protein content and germ load significantly below legally prescribed threshold values, independent of the interval between pre-cleaning and reprocessing. Conclusions Our findings indicate that flexible endoscopes could be stored overnight after pre-cleaning without any influence on the quality of reprocessing. While ensuring patient safety, this could simplify logistical processes and enable cost savings.